THE RELATIONSHIP BETWEEN STUDENTS’ SELF-EFFICACY IN LEARNING ENGLISH AND THEIR ENGLISH LEARNING ACHIEVEMENT AT THE TENTH GRADE OF SMAN 04 SOUTH TAMBUN IN 2019/2020 ACADEMIC YEAR - Fernindy Fitra Gumanti; Nita Kaniadewi (ELLTER Journal, 2020)
The objective of this study was to find out the relation between students’ self-efficacy belief in learning English and their English learning achievement of the tenth grade students of SMAN 4 South Tambun in 2019/2020 academic year. This study used correlational study between two variables which was included in quantitative research. In this study, the writer took one class of tenth grade students which consist of 36 students as the sample. The writer found the correlation coefficient (r) result between students’ self-efficacy in learning English and their English learning achievement which was 0,628. Afterward, the writer compared r result to the interpretation of correlation table and showed there was positive correlation. Thus, It proves that self-efficacy belief encourages and helps students to improve their skills and self-confidence, and finally achieve better learning outcomes. Keywords: Self-Efficacy, Learning, Learning Achievement, English Learning Achievement.